INVESTIGATION OF DIFFUSED-ALLOYED WASTE OF STEEL AND CAST-IRON GRIT FOR PRODUCTION OF PROTECTIVE COATS - E. E. Panteleenko; V. G. Shcherbakov (Литьë и металлургия)
The article is dedicated to solving of actual problem on creation of inexpensive alloying materials in the form of composite powders of the steel and cast iron grit waste by means of their diffusion alloying by boron.